A Novel Dynamic Routing Approach to Distributed Wireless Sensor Network in Aircraft Environment. (13th January 2021) - Sun, Hui; Bai, Chengrui; Li, Yahui; Yang, Kaixin
Abstract : The trend to implement the monitoring system with a wireless sensor network has been becoming urgent due to guaranteed flight safety and the passengers comfortability in travel. In this paper, a new dynamic routing algorithm is proposed to prolong the lifetime of the monitoring system with a distributed network based on the K -coverage method, and filter algorithm to be used for data fusion. Finally, the simulation results validate the effectiveness of the proposed approach.